Comparison of three different methods of internal sinus lifting for elevation heights of 7 mm: an ex vivo study - Aghiad Yassin Alsabbagh; Mohammed Monzer Alsabbagh; Batol Darjazini Nahas; Salam Rajih (SpringerOpen, 2017)
Abstract Background Various techniques are available for elevating the sinus membrane. The aim of this study is to evaluate three methods of indirect sinus floor elevation regarding elevation heights of 7 mm on the outcomes of membrane perforation, length of perforation, and time required to perform the procedure. Methods Three different methods for indirect sinus lifting, bone added osteotome sinus floor elevation (BAOSFE), sinus floor elevation with an inflatable balloon, and crestal approach system (CAS kit) from OSSTEM, were assessed for their ability to lift the sinus without causing laceration of the Schneiderian membrane. The study was performed on 18 freshly slaughtered sheep heads (36 sinus lifts were done, 12 for each method). CBCT images of the heads were taken to assess the best location for the sinus lift. Then, the heads were bisected and the membrane was exposed from the medial aspect. After that, each method was performed. The intended elevation height was 7 mm. If the 7 mm were not reached, the maximum height of elevation was measured. Results The method used was significantly associated with the occurrence of perforation (p value = 0.014) where BAOSFE was associated with the largest number of perforations (58.4%, n = 7) compared to 8.3% and 8.3% for the balloon and CAS kit methods, respectively. The odds ratio for perforation occurrence from BAOSFE compared to the CAS kit was significant (OR = 0.091, p = .022). No significant odds ratio was found for the balloon method compared to CAS kit. Additionally, the method used was significantly associated with time of operation and with the length of perforation (p value < 0.001) where CAS kit required the longest time and BAOSFE caused the biggest perforations. Conclusions The study shows that both the balloon and the CAS kit were superior to the BAOSFE in terms of safety in elevating the sinus membrane. Further, in vivo studies have to prove these findings.